Japanese kana workbook - O'Neill, P. G. (Kodansha international, 1967)
The Japanese kana signs are so basic and elementary a part of Japanese writing that the problems they can pose for the beginner is often overlooked. They form a first barrier to the reading of Japanese script which is uaually more difficult for the student than it need be.